2006
DOI: 10.1038/sj.npp.1301110
|View full text |Cite
|
Sign up to set email alerts
|

Time Course of the Antipsychotic Effect and the Underlying Behavioral Mechanisms

Abstract: Antipsychotic drugs work for patients only when given repeatedly. The overall temporal pattern of symptom improvement is not clear. Some recent data question the traditional 'delayed-onset' hypothesis and suggest that the onset of antipsychotic response may be relatively early, and the improvement may grow with repeated treatment. The present study systematically examined the time course of the antipsychotic effect and the underlying behavioral mechanisms using a conditioned avoidance response (CAR) model. Rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
101
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(128 citation statements)
references
References 48 publications
24
101
3
Order By: Relevance
“…The effect of NK 3 knockout on active avoidance seen in the present study stands in contrast to the effects of currently known antipsychotics, which impair performance in the active avoidance task when given both acutely and chronically (Li et al 2007;Wadenberg and Hicks 1999). Indeed, deficits in active avoidance have been suggested as a screening method for detecting antipsychotic activity.…”
Section: Discussioncontrasting
confidence: 54%
“…The effect of NK 3 knockout on active avoidance seen in the present study stands in contrast to the effects of currently known antipsychotics, which impair performance in the active avoidance task when given both acutely and chronically (Li et al 2007;Wadenberg and Hicks 1999). Indeed, deficits in active avoidance have been suggested as a screening method for detecting antipsychotic activity.…”
Section: Discussioncontrasting
confidence: 54%
“…Based on measures of D2 receptor occupancy, Kapur et al (2003) concluded that in order to achieve D2 receptor occupancy in the rat that corresponds with D2 occupancy in patients following clinically effective doses (65-80% D2 occupancy), 0.04-0.08 mg per kg haloperidol needs to be administered. Defining a low dose in terms of lower, 50% D2 receptor occupancy, 0.025 mg per kg (Li et al, 2007a) was selected as a dose (see also Table 1 in Kapur et al, 2003). Haloperidol was administered for 10 days and given 30 min prior to the task onset, so that performance was assessed while plasma levels rose and before reaching the half-life point for haloperidol in rats (Cheng and Paalzow, 1992).…”
Section: Treatment With Clozapine or Haloperidolmentioning
confidence: 99%
“…We recently developed a rat conditioned avoidance responding model based on a repeated treatment regimen and examined its validity in modeling the time course of antipsychotic effect (Li et al, 2007). We found that rats repeatedly treated with haloperidol, olanzapine, or risperidone exhibited a decrease in avoidance responding starting on the first day of treatment.…”
Section: Experiments 3: Effects Of Repeated Olanzapine and Chlordiazepmentioning
confidence: 99%
“…We included 10.0 mg/kg chlordiazepoxide as a pharmacological control. This dose of chlordiazepoxide is ineffective in disrupting avoidance responding (Li et al, 2004(Li et al, , 2007Mead et al, 2008), but it is effective in several aversively conditioned paradigms, such as Pavlovian fear conditioning and passive avoidance responding (Burghardt et al, 2004;Joordens et al, 1998;Klint, 1991;Mead et al, 2008).…”
Section: Drugsmentioning
confidence: 99%
See 1 more Smart Citation